Stronger association of polycyclic aromatic hydrocarbons with soot than with char in soils and sediments. (January 2015) - Han, Y.M.; Bandowe, B.A.M.; Wei, C.; Cao, J.J.; Wilcke, W.; Wang, G.H.; Ni, H.Y.; Jin, Z.D.; An, Z.S.; Yan, B.Z.
Highlights: TOC, EC, char, soot, and 12 parent PAHs were measured in sediments and soils. Lower concentrations of EC, char, soot and ∑12PAHs were observed in sediments. Differences in transportation and degradation contribute to the relative percentages of char and soot. Sorption capacity of soot yields a closer association with PAHs. Stronger correlation between PAHs and different carbon fractions occurs in sediments than in soils. Abstract: The knowledge of the association of polycyclic aromatic hydrocarbons (PAHs) with organic matter and carbonaceous materials is critical for a better understanding of their environmental transport, fate, and toxicological effects. Extensive studies have been done with regard to the relationship of PAHs with total organic carbon (TOC) and elemental carbon (EC) in different environmental matrices. The relationship between PAHs and the two subtypes of EC, char (combustion residues) and soot (produced via gas-to-particle conversion) also has been tested in field and laboratory experiments using reference materials. However, a direct comparison of associations of PAHs between with char and with soot in real environmental matrices has to our knowledge not yet been reported because of a lack of methodology to differentiate them. In this study, char and soot were measured using the IMPROVE method to test their associations with 12 EPA priority PAHs measured in topsoil samples ( N = 22, top 10 cm) collected from the Guanzhong Plain and in surface sediment samples ( N = 32, top 5 cm) from the Wei River (central China). In both soils and sediments, ∑12PAHs were more strongly associated with soot than with char, mainly due to the fact that soot and PAHs were produced in the same gas phase during combustion, had a strong affinity for each other, and were transported and deposited together, while char, the combustion residue, was transported differently to PAHs due to its large particle size. Stronger correlations between PAHs and the different carbon fractions (TOC, soot, and char) in sediments than in soils were observed, which is associated with the redistribution of PAHs among the organic matter pools in water because of the processes during soil erosion and sedimentation in the river.